Analysis of North Sulawesi’s Beef Cattle Farming Empowerment Strategy with Websites - Very L.H Rembang; Judy M. Tumewu; Jolyanis Lainawa (International Journal of Applied Business and International Management, 2020)
The production of beef cattle farming enterprises in North Sulawesi has not been able to meet people consumption needs. This condition is due to their slow absorption of breeding technology information among farmers, while the existing internet technology is merely used for entertainment needs. This research paper is to encourage the formation of an empowering model for beef cattle farmers in rural areas using websites. The findings suggested that the design model should be based upon farmer’s capabilities and existence of farmers, since they have adequate information about websites as outreach media needed for farmer empowerment.